2016
DOI: 10.1515/botcro-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Traits on Polyphenols Level in Moltkia petraea (Tratt.) Griseb. (Boraginaceae)

Abstract: -The Illyric-Balkan endemic species Moltkia petraea (Tratt.) Griseb. is very interesting as a potential horticultural and medicinal plant. The aim of this study was to investigate soil conditions of M. petraea habitats, the phenolic content in plant parts, and the infl uence of soil properties on the phenolic contents. The results were evaluated using Spearman rank order correlations. Analyzed soil samples contained very low to intermediate levels of physiologically active phosphorus, but were very rich in pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The content of biologically active compounds in plants depends on various factors: influence of soil traits, plant age, harvesting time, tissue type etc. (Končić et al, 2010, Kremer et al, 2016, Kolodziej and Sugier, 2013. Kremer et al (2016) analyzed biochemical properties of M. petraea and reported the highest content of polyphenols, flavonoids and phenolic acids in leaves, the highest content of tannins highest in flowers, with the lowest content of the analyzed bioactive compounds in stems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of biologically active compounds in plants depends on various factors: influence of soil traits, plant age, harvesting time, tissue type etc. (Končić et al, 2010, Kremer et al, 2016, Kolodziej and Sugier, 2013. Kremer et al (2016) analyzed biochemical properties of M. petraea and reported the highest content of polyphenols, flavonoids and phenolic acids in leaves, the highest content of tannins highest in flowers, with the lowest content of the analyzed bioactive compounds in stems.…”
Section: Resultsmentioning
confidence: 99%
“…comprises five species (Cohen, 2014), with Moltkia petraea (Tratt.) Griseb growing mostly in Mediterranean and Submediterranean regions (Kremer et al, 2016). This species is a dense, dwarf shrub, up to 40 cm high, with deep violet-blue tubular flowers, in simple forked or branching revolute cymes, blooming from spring well into the summer (Fernandes, 1972;Polunin, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Boraginaceae) had the highest TP content in flowers (Vuković Rodríguez et al 2016). Additionally, investigations of TP content in ten Moltkia petraea populations obtained by Kremer et al (2016) showed that TP content was the highest in leaves in six populations. But in another four populations the TP content was the highest in flowers.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, TP content ranged from 4.43% in stem to 12.41% in leaves of Satureja montana, and from 5.96% in stem to 20.04% in leaves of S. subspicata (Dunkić et al 2012). Additionally, TP content in Moltkia petraea ranged from 3.26% in stem to 6.61% in leaves (Kremer et al 2016).…”
Section: Discussionmentioning
confidence: 99%